2019
DOI: 10.3390/rs11242957
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of the Consistency of Landsat 8 and Sentinel-2 Time Series Products in An Urban Area—An Example in Beijing, China

Abstract: Global urbanization is occurring rapidly, and numerous moderate resolution remote sensing data are being used to monitor this process. Landsat 8 OLI and Sentinel-2 MSI data are combined in many applications but few studies haves focused on either urban change or consistency between these two data in time series. To evaluate the varying correlation between the two sensors in a time series, the correlation coefficient (R) and root-mean-square deviation (RMSD) of seven band pairs and three indices (NDVI, NDBI, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…However, they did not use simultaneously acquired image pairs from L8 and S2. Better NDVI consistency statistics between L8 and S2 were reported by Nie et al [38] in an urban area in which RMSE values from 0.035 to 0.081 were computed. Li et al [46] reported that the NDVI calculated using the Sen2Cor surface reflectance of bands B8A and B04 was also reliable.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…However, they did not use simultaneously acquired image pairs from L8 and S2. Better NDVI consistency statistics between L8 and S2 were reported by Nie et al [38] in an urban area in which RMSE values from 0.035 to 0.081 were computed. Li et al [46] reported that the NDVI calculated using the Sen2Cor surface reflectance of bands B8A and B04 was also reliable.…”
Section: Discussionmentioning
confidence: 64%
“…The sun glint effect observed in the present work was related to the sun elevation, appearing with sun elevation higher than 52 degrees (i.e., mainly in summer season). Working in urban areas (generally bright and anthropic areas such as PCG ones), Nie et al [38] reported worse consistency in summer data pairs, presenting the major discrepancies in the SWIR2 band. In addition, an interesting relationship between the sun glint on some plastic sheets and the satellite orbit (orbits leaving the sun on their back minimized this solar reflections) was found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Arekhi et al did investigate sensor fusion across seasons for both individual bands and vegetation indices and concluded that absent systematic errors in data retrieval or random errors in atmospheric interference, L8 OLI and S2A MSI can be used for long term monitoring [36]. Other studies into sensor fusion did not consider more than two satellite systems of similar spectral and spatial features [37] or focused on categorically different land cover types such as urban areas [38].…”
Section: Introductionmentioning
confidence: 99%